PENDAYAGUNAAN KELEMBAGAAN LOKAL DALAM MENINGKATKAN KETAHANAN PANGAN MASYARAKAT PADA MASA PANDEMI COVID-19 - Sari, Novita; Rukminto Adi, Isbandi (UI Scholars Hub, 2022)
The Covid-19 pandemic is a disease outbreak that has hit Indonesia since 2020. The impact of this epidemic changed the order and habits of society in general. This pandemic not only destroyed the health and economic structure, but also triggered a world food crisis, including Indonesia. Regions in Indonesia are experiencing various problems and crises, one of which is Kampar Regency. The fulfillment of food needs in Kampar Regency is mostly imported from West Sumatra via the West Sumatra-Riau national road. The dependence of Kampar Regency on West Sumatra can be seen when landslides occur, so there is a spike in food prices, especially staple foods. Now that uncertain conditions due to Covid-19 have limited the space for distributing food, crisis conditions like this require development that involves the community and local institutions directly by empowering all potential people. The local government of Kampar Regency carries out plans that produce policies to realize local development of food security through the use of community yards or land as an effort to optimize community independence in maintaining food security. This study will describe how the planning process for the utilization of local institutions in Kampar Regency through existing conditions, which are then analyzed, leads to policy interpretation. This research uses a qualitative approach with a descriptive type of research. Meanwhile, for data collection using an in-depth interview method. The results of this study describe the development of strategies and obstacles as well as efforts to utilize local institutions in the planning process, explaining the involvement of actors in the planning process as well as obstacles and ways to overcome certain obstacles.